Analisis Ekowisata di Kawasan Konservasi Perairan Raja Ampat: Daya Dukung dan Evaluasi Wisatawan dari Situs TripAdvisor - Larasati, Sharfina Elda; Aminun, Nur Fadhlan (Pusat Studi Pariwisata Universitas Gadjah Mada, 2023)
Managing natural tourism in the Water Conservation Area (KKP) is challenging as it must adhere to conservation principles while preserving user access rights and visitor experiences. To address this, we conducted a literature review to aid KKP Raja Ampat in developing sustainable ecotourism. Using TripAdvisor reviews, we assessed tourist perceptions, analyzing 35 reviews covering overall satisfaction, environmental aspects, service, and management. Carrying capacity calculations, following the Cifuentes method, were applied in a case study of KKP Dampier Strait and various marine tourism areas in Raja Ampat. Findings reveal the real carrying capacity in KKP Dampier Strait is 8 - 854 visitors daily, while in Raja Ampat marine tourism areas, it ranges from 17 - 1,881 visitors depending on location and activities. The tourism potential can be further developed with suggestions based on carrying capacity calculations. TripAdvisor reviews indicate excellent tourist experiences. Ultimately, these reviews serve as a valuable tool for decision-makers, identifying negative aspects and proposing solutions for effective management.